HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP TENTANG AKTIVITAS SEKSUAL DENGAN AKTIVITAS SEKSUAL PADA MASA MENOPAUSE DI DESA LEMBANG KABUPATEN BENGKAYANG - Adi, Adi; Budiastutik, Indah; Hastuti, Lidia (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Background: The menopause is marked by the ending of menstruation and happen to women the age of 45-50 years old. In this period, there are many change of life, ones of the is sexual problem. Based on first survey in lembang village, there is a case a women menopause reported her husband to villageâ€™s leaders because her husband always forced her to do inter course every day, and there is a mitos named â€œpari ka jubataâ€, this is means God forbid to do sexual activity when is old age. This is caused by knowledge and attitudes of women are still less about menopause, especially about sexual activity.Purpose: To analyze the correlation of knowledge and attitudes about sexual activity with sexual activity in menopause period in Lembang village subdistrict of Bengkayang 2014.Methods: This is an analiytic survey research using cross sectional desing with samples as many as 75 (accidental sampling) people. The statistic test used is spearman rank test by 95% level of singnificance (p value) and correlation of power by spearman rank correlation (r value).Results: There is correlation between knowledge with sexual activity in menopause period (p = 0,000) with a moderate correlation of power (r = 0.423). There is correlation between attitudes with sexual activity in menopause period (p = 0,001) with a weak correlation of power (r = 0, 377).Advice given is the women of menopause should really open mind, active and willing to take the time receive information about menopause especially sexual activity, doing gymnastic for old age and collaborate with villageâ€™s programs by counseling for increased knowledge about healty sexual activity in menopause period.Keywords: Knowledge, Attitudes, Menopause, Aging and Sexual Activity